Obtenção do sistema TiO2:Ag na forma de filmes nanoestruturados em filtros cerâmicos para aplicação em fotocatálise - Oliveira, Regiane Cristina de (2014)
In this study, it was aimed to obtain powders and thin films of titanium dioxide (TiO2) with silver (Ag) deposited on ceramic filters, synthesized by the polymeric precursor method for degradation of rhodamine B dye under ultraviolet and visible radiation. Initially, it was optimized the obtention of the TiO2 powders with anatase phase and high photocatalytic efficiency. In this way, it was varied the pH of the synthesis (1 and 7), the citric acid and titanium molar ratio (1:1.5, 1:2, 1:3 and 1:4) and the heat treatment temperature (300, 400, 500, 600 and 700°C). By means of the X-ray diffraction (XRD) technique and photodegradation results of the rhodamine B dye, it was determined that the TiO2 powders obtained at pH 1, the molar ratio of citric acid:Ti 1:3 and heat treating temperature of 400°C (for 2 h) crystallizes in the anatase phase and exhibit a higher photocatalytic efficiency. These parameters were used to obtain TiO2:Ag powders with variation of the Ag mol percentage (0.5, 1, 3 and 5%). The XRD and photocatalysis results indicated that 1% provided TiO2:Ag powders with anatase phase and the greatest photocatalytic efficiency. These results suggested that the parameters applied in the synthesis of the polymer solution used to prepare the films of TiO2 and TiO2:Ag. In this step, were varied the solution viscosity at 15, 20 and 25 cP; the number of layers in 2, 3 and 5, and the porosity of the ceramic substrate in 10 and 15 ppi. These films showed an average efficiency of photodegradation of approximately 30%, regardless of the synthesis parameters. This photocatalytic efficiency can be associated with low homogeneity of the films, which could be verified by Scanning Electron Microscope (SEM).